Bushido: The Spirit of Japan. Tool to mold the ethical future of Iceland? - Hákon Óttar Hjörvarsson 1984- (2012)
Atheism has been gaining ground in the Western world since the turn of the millennium and according to national statistics more and more people are coming away from organized religion. Religious education in schools has been banned and this may be worrying to some since it might be difficult to impart moral education without religious influence. After Inazo Nitobe had a conversation with a friend sometime in the year 1894 concerning just that topic, he decided that he needed to explain how the Japanese managed to teach moral ethics and social values through the disciplines of Bushido and wrote the book Bushido: The Soul of Japan. To find out whether or not Bushido is adequate, I will first look at the common rules of Christianity, then look at the seven major disciplines of Bushido. Then I will show how the institution of Christianity has been used as a tool for social behavioral modification and then go into comparison marking each of the seven major disciplines of Bushido in turn. The goal of this thesis is not to prove whether or not it is possible to impart moral education without religious influence, but whether or not Bushido can replace Christianity as a tool to teach moral ethics and social behavior in the growing atheism in Iceland.